Educational Leadership In Pesantren : Managing To Improve The Quality Of Qur’an Memorization - Ningsih, Wiwik Minda; Kurniawan, Asep (JIEM (Journal of Islamic Education Management), 2025)
The quality of Al-Qur'an memorization reflects the extent of a person's ability to master and maintain their memorization. To improve this quality, it is necessary to apply management that includes the functions of planning, organizing, implementing, and supervising, by optimally utilizing available human resources and facilities. This study aims to describe the management of Islamic Boarding Schools, examine the quality of students' memorization, and analyze the contribution of management in improving the quality of students' memorization of the Al-Qur'an. The method used is a qualitative approach of a descriptive case study type, with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that management in Islamic Boarding Schools includes the preparation of a structured tahfidz program, the arrangement of supervisor tasks and deposit schedules, the implementation of routine tahfidz activities, and supervision through daily evaluations and exams every time one juz is completed. Efforts to improve the quality of memorization are carried out through daily deposits after dawn, murajaah after asar and maghrib, and the provision of special guidance for students who experience difficulties. Overall, the management of the Islamic Boarding School has proven to have a significant role in supporting the success of students' memorization, through an organized system, discipline in implementation, and continuous evaluation, thus creating a conducive environment to maintain and strengthen memorization of the Qur'an to the maximum.